(untitled) (Cardiovascular Journal, 2014)
Background: Spontaneous echocardiographic contrast (SEC) is a risk factor for left atrial thrombus formation and an important indicator of potential systemic embolism originated from heart. An established relation exists between the inflammatory status and the prothrombotic state. The present study was conducted to evaluate the association between left atrial spontaneous echocardiographic contrast with inflammatory markers in mitral stenosis patients. Methods: This observational analytical study was undertaken in the department of Cardiology, National Institute of Cardiovascular diseases (NICVD), Dhaka. A total of 70 patients with mitral stenosis were categorized into two groups: group I with left atrial SEC and group II without left atrial SEC. All patients underwent transthoracic as well as transoesophageal echocardiography. Complete blood count with ESR was done and neutrophil lymphocyte ratio was calculated. The high sensitive C-reactive protein (hs-CRP) was assayed. Results: The hs-CRP levels were significantly greater in the SEC-positive group (5.6±2.1vs 1.5±0.7, p=0.001). The mean ESR level was significantly greater in the SEC-positive group (32.6±15.5 mmvs15.8±4.7 mm).The neutrophil levels ((76.1±1.9 vs 63.7±3.3) were significantly greater in the SEC-positive group, and the lymphocyte levels (33.3±3.0 vs 21.5±1.3) were significantly greater in the SEC-negative group (p=0.001 for each). The neutrophil/lymphocyte (N/L) ratio was also significantly greater in the SEC-positive group (3.4±0.4 vs2.1±0.6, p=0.001).On multivariate analysis hs-CRP, neutrophil/lymphocyte ratio, raised ESR, mitral valve area and left atrial diameter were independent risk factors for SEC in patients with mitral stenosis. Conclusion: From this study it may be concluded that left atrial SEC is associated with raised inflammatory markers in majority of patients with mitral stenosis. So, SEC may be considered as a reflection of ongoing inflammatory process in patients with mitral stenosis. DOI: http://dx.doi.org/10.3329/cardio.v7i1.20797 Cardiovasc. j. 2014; 7(1): 24-30